2019
DOI: 10.1186/s12879-019-3718-8
|View full text |Cite
|
Sign up to set email alerts
|

A survey of fungal microbiota in airways of healthy volunteer subjects from Puglia (Apulia), Italy

Abstract: BackgroundThe human respiratory tract represents the major portal of entry for numerous microorganisms, primarily those occurring as airborne particles such as viral and bacterial entities, or fungal spores. Microorganism characteristics coupled with the local host immune response will determine whether they will be cleared or adhere and colonize the airways leading to acute or chronic pulmonary disease. Like bacteria, fungi can cause severe lung diseases, but their infection rates are much lower. The lung mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…The dominant fungal genera recovered in this study were completely distinct from those reported in another study, which documented the dominance of Aspergillus sydowii and Cladosporium spp . 36 This distinction is likely due to the differences caused by culture-dependent and culture-independent sequencing methods. 72 In addition, some common fungi in the sputum and oral cavity, including Candida , Aspergillus , and Saccharomyces , were less frequent in the EBC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant fungal genera recovered in this study were completely distinct from those reported in another study, which documented the dominance of Aspergillus sydowii and Cladosporium spp . 36 This distinction is likely due to the differences caused by culture-dependent and culture-independent sequencing methods. 72 In addition, some common fungi in the sputum and oral cavity, including Candida , Aspergillus , and Saccharomyces , were less frequent in the EBC.…”
Section: Resultsmentioning
confidence: 99%
“… 100 , 101 Based on this, it is probable that floor dust fungi were partly from the human exhaled breath, and there is a potential relationship between exhaled fungi and asthma severity. 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu hastalarda Asperg llus (özell kle A. fum gatus), C. alb cans, C. paraps los s ve Malassez a türler zole ed lm şt r 44. Astım ve KF' de Asperg llus tarafından ndüklenen alerj k yanıt "allerj k bronkopulmoner hastalık" şekl nde tanımlanmaktadır.Carpagnano ve ark 45. 43 akc ğer kanser hasta ve 21 sağlıklı b reylerde ekshalasyon le ver len havada ve bronş yal fırça örnekler nde fung varlığını araştırmışlardır.…”
unclassified
“…Although the title of the Special Issue is ‘Airborne Microbiome’ the manuscripts received have highlighted a variety of peripheral, yet related aspects of this. The contributions are a mixture of primary research, reviews and commentaries, including: new methods to explore environmental niches where such microbes may grow [1], their detection and characterisation in the human host [24], which pathogens are present in the respiratory tract and can be exhaled in human breath to potentially spread via the airborne route [5, 6], and some strategies for their control [7]. Finally, a historical-to-current overview explores human-microbial interactions, including problems with sampling and detection methods, drug resistance, the role of super-spreaders and issues around research funding [8].…”
mentioning
confidence: 99%